Eco-friendly synthesis of Carbon Quantum Dots (CQDs) from hazelnut husk for sensitive Aflatoxin B1 (AFB1) detection - Hatice Yuncu; Hayrunnisa Nadaroglu; Ebru Bozkurt (Toxicology Reports, 2024)
In this study, green fluorescent carbon quantum dots (CQDs) with remarkable stability, water solubility, and biocompatibility were synthesized from hazelnut husk (HH) waste material using a novel approach by the pyrolysis method. The optical properties of the synthesized HH-CQDs were characterized by UV-Vis and fluorescence spectroscopy (PL), while their structural properties were characterized using various techniques, including transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). TEM images revealed that HH-CQDs had a spherical shape with diameters ranging from 2 to 10 nm. The fluorescence quantum yield of these CQDs was measured as 0.04. Furthermore, CQDs were very effective at finding aflatoxin B1 (AFB1) using a fluorescence resonance energy transfer (FRET) mechanism, with a clear fluorescence emission peak seen at 451 nm. The photoluminescent properties of CQDs were evaluated under various pH conditions, showing a blue shift and increased fluorescence intensity at pH 9–10, suggesting their potential use in pH-sensitive sensor applications. This study demonstrates the selective and sensitive detection of AFB1 using HH-CQDs, with a strong linear relationship (R² = 0.9936) between fluorescence intensity and AFB1 concentration in the range of 25–250 ppm, and high accuracy in real food samples, including 81.56 % in corn, 98.64 % in milk, and 95.73 % in peanuts. This eco-friendly and cost-effective synthesis method offers a promising alternative for AFB1 detection in food samples by utilizing waste material to create valuable analytical tools.